Synthesis, Structural Characterization, and Cytotoxic Activity of Novel Paramagnetic Platinum Hematoporphyrin IX Complexes: Potent Antitumor Agents. (7th August 2007) - Gencheva, G.; Tsekova, D.; Gochev, G.; Momekov, G.; Tyuliev, G.; Skumryev, V.; Karaivanova, M.; Bontchev, P. R.
Abstract : Three novel stable Pt(III) complexes with distorted octahedral structure and( d z 2 ) 1 ground state have been obtained in the course of Pt(II)-hematoporphyrin IX ((7, 12-bis(1-hydroxyethyl)-3, 8, 13, 17-tetramethyl-21H-23H-porphyn-2, 18-dipropionic acid), Hp) interaction in alkaline aqueous medium and aerobic conditions. A redox interaction also takes place together with the complexation process leading to the formation of Pt(III) species and organic radicals. The processes in the reaction system and the structure of the complexes formed cis -[Pt(III)( NH 3 ) 2 (Hp − 3 H )( H 2 O ) 2 ]⋅ H 2 O 1, [Pt(III)(Hp − 3 H )( H 2 O ) 2 ]⋅ H 2 O 2, and [Pt((O, O)Hp − 2 H )Cl( H 2 O ) 3 ]3, were studied by UV-Vis, IR, EPR and XPS spectra, thermal (TGS, DSC), potentiometric and magnetic methods. The newly synthesized complexes show promising cytotoxic activity comparable with that of cis -platin in in vitro tests against a panel of human leukemia cell lines. The observed cytotoxicity of the complex2 against SKW-3 cells (KE-37 derivative) is due to induction of cell death through apoptosis.